Relationship between the physical activity practice and the social support perceived in adolescents of the province of Soria - Sanz-Martín, D.; Ruiz-Tendero, G.; Fernández-García, E. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
There is a social concern about knowing the levels of physical activity practice of adolescents, in order to carry out improvement proposals if necessary. This study was designed with the purpose of getting to know those levels of adolescents of Soria and the social support they perceive for their practice, from family and friends, depending on the gender of the students, and identifying the type of relationship between their practice and social support perceived. The sample selected was 694 adolescents of Compulsory Secondary Education from the province of Soria, to whom Four by one day physical activity questionnaire, parent support scale and peer support scale, were administered. The results showed significant differences in physical activity levels and social support according to the gender of the students and a significant correlation has been obtained between these levels and the support perceived.